Implementasi nilai pancasila dalam menghadapi tantangan multikulturalisme dan pluralisme di Indonesia - Haniifah, Fatwa Ulayya (Maliki Interdisciplinary Journal, 2026)
Indonesia is a country with a very high level of diversity in terms of ethnicity, religion, culture, and language. This condition makes multiculturalism and pluralism the main characteristics of Indonesian society. However, amid the development of globalization and advances in information technology, diversity also presents various challenges such as intolerance, discrimination, social conflict, and the strengthening of identity politics. This article aims to analyze the implementation of Pancasila values in facing the challenges of multiculturalism and pluralism in Indonesia. The method used in this article is a literature study with a descriptive-analytical approach through the examination of books, scientific journals, regulations, and various relevant academic sources. The results of the discussion indicate that the values of Pancasila have a strategic role as guidelines in maintaining unity, tolerance, and social harmony within Indonesia’s diverse society. Nevertheless, the implementation of Pancasila values still faces several obstacles, including the low level of public understanding of national values, the influence of social media, and the emergence of group exclusivism. Therefore, it is necessary to strengthen character education, improve digital literacy, and enhance cooperation among the government, educational institutions, and society in internalizing Pancasila values in everyday life. Through consistent implementation, Pancasila can remain the primary foundation for maintaining national integration amid the dynamics of Indonesia’s multicultural society.